Analysis of tajweed errors in Quranic recitation - Hassan, Surul Shahbudin; Zailaini, Muhammad Azhar (Elsevier - Science Direct, 2013)
The aim of this study is to identify the various types of tajweed errors made by students during Quran recitation. This study was carried out on 20 students who took the Tilawah Al-Quran (Quran Recitation) level 2 course as part of their first degree programme at the IIUM. Analysis of the errors was carried out on recordings of the espondents' recitation using a comprehensive set of instruments to dentify the type and category of errors comitted. Only errors that occurred at least 1% percent of the time are taken into consideration in this analysis. As a result, a total of six elementary errors have been found. It is hoped that this study will pave the way for a more effective method of teaching the subject of Quranic Recitation which continues to focus on the practical aspects of tajweed knowledge.